Sociolinguistic Aspect in Training Future Foreign Language Teachers - Korol, Svitlana (Pedagogical Discourse, 2016)
The article focuses on the importance of sociolinguistic competence in training future foreign language teachers. The author stresses that the sociolinguistic aspect of teaching a foreign language is crucial to the formation of foreign communicative competence of a future foreign language teacher because sociolinguistic knowledge provides free integration of a personality into the modern foreign language environment. Nowadays, teaching a foreign language presupposes taking into account the influence of social, cultural and political events on the language development. The author states that formation of sociolinguistic competence has to be based on the use of appropriate authentic sources in the education process due to the fact that the sociolinguistic component of teaching has to reflect the modern social conditions of a language use and comprise the current social conventions. The conclusion has been made that the properly developed sociolinguistic competence is an integral part of a foreign language teacher’s professional competence. Thus, teaching a foreign language it is necessary not only to possess this competence, but also be able to develop it in students. Key words: sociolinguistic competence, authentic teaching materials, communicative competence, foreign language teachers.